A murine even-skipped homologue, Evx 1, is expressed during early embryogenesis and neurogenesis in a biphasic manner. - Bastian, H (1990)
Using the Drosophila even-skipped (eve) homeobox as a probe, we have isolated two murine genes, Evx 1 and Evx 2, from a genomic library. Evx 1, Evx 2, eve and the Xenopus Xhox-3 constitute a family of related genes based on similar homeodomain sequences. In addition, Evx 1 and Evx 2 share extended amino acid conservation outside of the homeobox. The Evx 1 protein consists of 416 amino acids as deduced from the longest open reading frame of Evx 1 cDNAs. Evx 1 is located 3.7 cM from the Hox 5 locus on mouse chromosome 2. It is expressed in undifferentiated F9 stem cells but not in cells differentiated with retinoic acid and cAMP. During embryogenesis, Evx 1 shows a biphasic expression pattern. From days 7 to 9 p.c. Evx 1 expression emerges at the posterior end of the embryo within the primitive ectoderm, and later in the mesoderm and neuroectoderm. From days 10 to 12.5 p.c. Evx 1 transcripts are restricted to specific cells within the neural tube and hindbrain along their entire lengths and coincides temporally, as well as spatially, with maturation of early forming interneurons, possibly commissural interneurons. The early and late transcription pattern is compatible with a role of Evx 1 in specifying posterior positional information along the embryonic axis similar to the Xenopus Xhox-3 and in specifying neuronal cell fates within the differentiating neural tube in analogy to eve in the embryonic central nervous system of Drosophila, respectively.